Hypertension in childhood obesity - Wühl, Elke (Acta paediatrica, 2019)
Aim The prevalence of childhood hypertension is rising in parallel with global increases in the prevalence of overweight and obesity. We looked at key papers and documents covering three decades. Methods This mini review examined a wide range of material published in English, with the main focus on 1993-2018, including clinical trials, meta-analyses, guidelines and data produced by the World Health Organization and the World Obesity Federation. Results The literature showed that body weight and blood pressure are closely correlated and obesity-related hypertension contributes further to the clustering of cardiovascular risk factors in obesity. Because the duration of hypertension affects the risk of end-organ damage, timely diagnosis and initiation of treatment are important. First-line interventions should aim for blood pressure control and weight reduction. However, lifestyle modifications are often not successful with regard to attaining and maintaining long-term blood pressure and weight control, despite a multidisciplinary approach. Antihypertensive treatment is recommended for all hypertensive children with failure of nonpharmacological treatment, diabetes, secondary hypertension, stage 2 hypertension or target organ damage. Conclusion We found that obesity-related hypertension was associated with a significantly increased cardiovascular morbidity and mortality, and early diagnosis and treatment for blood pressure control and weight reduction is essential.